Pengaruh Subtitusi Urea oleh Azolla Terhadap Pertumbuhan Tanaman Kacang Hijau (Vigna radiata [L.] R. wilcz.) Kultivar Perkutut di Kotabumi - Eko Abadi Novrimansyah (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Research on Urea substitution by Azolla is very much needed, because Azolla is expected to be able to reduce the use of urea dose without reducing plant growth. The purpose of this study was to determine the effect of giving substitution of Urea by Azolla on the growth of the Perkutut cultivar mung bean plant in Kotabumi. The treatment design was arranged in a single unstructured factor design, and the experimental design was in a completely randomized group design (RKTS) with 4 replications per treatment. The similarity between treatments was tested with the Bartlett Test, and to test the addition of the model was tested with the Tukey Test. If both of these assumptions are met, then the analysis of variance and the separation of mean values are continued using the Least Significant Difference test (BNT) at the 5% level. The treatment substitution used is P0 = control; P1 = 0% Azolla + 100% Urea; P2 = 20% Azolla + 80% Urea; P3 = 40% Azolla + 60% Urea; P4 = 60% Azolla + 40% Urea; P5 = 80% Azolla + 20% Urea; P6 = 100% Azolla + 0% Urea. The results showed that the fertilizer substitution treatment P3 = 40% Azolla + 60% Urea was able to increase the growth of mung bean cultivar plants which did not differ in growth when treated with P1 = 0% Azolla + 100% Urea.